2022
DOI: 10.1002/oby.23500
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity risk factors by race and ethnicity

Abstract: ObjectiveChildhood obesity is a public health concern that often worsens with age. Although several risk factors at the child and maternal levels have been identified in cross‐sectional studies, less is known about their long‐term contribution to racial/ethnic disparities in childhood obesity. This study examines child‐ and maternal‐level factors associated with the growth trajectories of White, Black, and Latino children.MethodsGroup‐based trajectory models were used to identify BMI z score trajectories from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Moreover, the incidence of obesity has more than doubled in children and quadrupled in adolescents in the past 30 years [ 3 , 4 ]. Children and adolescents with obesity are likely to experience obesity as adults; therefore, they are at an increased risk of adult health problems, such as heart disease, cardiovascular disease, type 2 diabetes, stroke, and osteoarthritis [ 5 , 6 , 7 ]. Additionally, chronic obesity is associated with an increased risk of cancer, including cancer of the breast, colon, endometrium, esophagus, kidney, pancreas, gall bladder, thyroid, ovary, cervix, and prostate, as well as multiple myeloma and Hodgkin’s lymphoma [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incidence of obesity has more than doubled in children and quadrupled in adolescents in the past 30 years [ 3 , 4 ]. Children and adolescents with obesity are likely to experience obesity as adults; therefore, they are at an increased risk of adult health problems, such as heart disease, cardiovascular disease, type 2 diabetes, stroke, and osteoarthritis [ 5 , 6 , 7 ]. Additionally, chronic obesity is associated with an increased risk of cancer, including cancer of the breast, colon, endometrium, esophagus, kidney, pancreas, gall bladder, thyroid, ovary, cervix, and prostate, as well as multiple myeloma and Hodgkin’s lymphoma [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that in the United States, trajectories and precursors of excessive weight gain from birth to 9 years of age vary by race and ethnicity ( 7 ). Our findings confirm that racial and ethnic differences in children's growth, and the factors that influence their growth, begin early in life.…”
Section: Discussionmentioning
confidence: 99%
“…In deconstructing the risk of early childhood obesity, studies have noted the following. First, racial and ethnic differences in BMI trajectories exist at birth and extend into the first few years of life [29–32,33 ▪▪ ]. Second, while social and socioeconomic factors can explain some of the risk for specific racial and ethnic groups, they do not explain all trends seen [29,30,33 ▪▪ ].…”
Section: Consequences Of Classifying Childhood Obesity As a Diseasementioning
confidence: 99%
“…First, racial and ethnic differences in BMI trajectories exist at birth and extend into the first few years of life [29–32,33 ▪▪ ]. Second, while social and socioeconomic factors can explain some of the risk for specific racial and ethnic groups, they do not explain all trends seen [29,30,33 ▪▪ ]. Third, the most concerning or ‘adverse’ BMI trajectories have been noted early in life in self-identified Black and Latino youth [30,32,34].…”
Section: Consequences Of Classifying Childhood Obesity As a Diseasementioning
confidence: 99%